Modelling and analysis of phase modulator based on silicon microring for long‐haul transmission. Issue 4 (1st August 2014) - Chen, Weiwei; Wang, Pengjun; Yang, Jianyi
Abstract : In this study, the authors numerically analyse the electrical and the optical properties of a silicon microring phase modulator using reverse‐biased pn junction configuration. The performance of the device is examined in terms of frequency chirp, switching time and intensity dip. They also evaluate the data transmission performance by varying the propagation distances at a bit rate of 10 Gbit/s. The simulation results show that the generated differential‐phase‐shift‐keying data at a drive signal with rise and fall times of 10 ps can achieve error‐free transmission for propagation distances up to 55.6 km, whereas the one at a drive signal with rise and fall times of 50 ps needs a 4.13 dB power penalty in a 17.5 km fibre transmission without dispersion compensation.